PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE BERBANTUAN MEDIA POSTER DILENGKAPI LKPD TEKA-TEKI SILANG TERHADAP HASIL BELAJAR SISWA DI SMP KATOLIK PADADITA - Gristi Rambu Yowa, Murti; Makaborang, Yohana; Rambu Hada Enda, Riwa (Universitas Cokroaminoto Palopo, 2025)
This study research to determine the effect of the cooperative learning model of the think talk write type assisted by poster media equipped with LKPD crossword puzzles. This research was conducted at Padadita Catholic Middle School with the research subjects being 34 class VIII A students as the control class and 35 class VIII B students as the experimental class in the 2024/2025 academic year. The type of research conducted is experimental research with a quantitative approach. The results of the study can be seen from the comparison of the average value of the control class 65 (pretest) 76.17 (posttest) and the experimental class the average value obtained was 68.28 (pretest) 81.71 (posttest). The results of the hypothesis testing using the dependent sample t test which has an Asymp. Sig (2 tailed) value of 0.001 means that the value is <0.05 so that H0 is rejected and H1 is accepted. It can be concluded that the cooperative learning model of the think talk write type assisted by poster media equipped with LKPD crossword puzzles has a significant effect on the learning outcomes of class VIII B students which is an experimental class at SMP Katolik padadita.